Pengukuran Kinerja Pemerintah Daerah Berdasarkan Value For Money - Novi Fadhila; Julianda Syahputra Tanjung (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to measure the performance of the local government of Deli Serdang Regency based on value for money. This study uses a descriptive approach, data collection in this study uses documentation techniques, and the analysis used is descriptive analysis techniques. The results showed that the performance of the local government of Deli Serdang Regency with the value for money method as measured by the economic ratio, efficiency ratio, and effectiveness ratio within a period of 5 years from 2016 to 2020 fluctuated where the economic ratio of Deli Serdang Regency experienced stability or can be called as quite economical in saving local government spending in Deli Serdang Regency, the effectiveness ratio fluctuates but is in a fairly effective condition, and the efficiency ratio has decreased